2008
DOI: 10.1002/jsfa.3333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of garlic powder on rumen ecology and digestibility of nutrients in ruminants

Abstract: BACKGROUND: The present study investigated the effect of garlic powder (GAP) supplementation on rumen fermentation pattern, nutrient digestibility and intake in ruminants fed on straw as a roughage source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
69
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 25 publications
24
69
3
Order By: Relevance
“…Kongmun et al (2010a) reported that the proportion of butyrate tended to increase when supplemented with garlic powder (10.8-12.4 mol/ 100 mol in in vitro). This result was similar to that obtained by Wanapat et al (2008b) in vivo, who found that the supplementation of garlic powder in native beef cattle resulted in an increase in the proportions of butyrate. Busquet et al (2005) also observed similar result.…”
Section: Rumen Fermentation Characteristicssupporting
confidence: 93%
See 3 more Smart Citations
“…Kongmun et al (2010a) reported that the proportion of butyrate tended to increase when supplemented with garlic powder (10.8-12.4 mol/ 100 mol in in vitro). This result was similar to that obtained by Wanapat et al (2008b) in vivo, who found that the supplementation of garlic powder in native beef cattle resulted in an increase in the proportions of butyrate. Busquet et al (2005) also observed similar result.…”
Section: Rumen Fermentation Characteristicssupporting
confidence: 93%
“…Based on an in vitro study, it was found that garlic powder and mangosteen peel powder resulted in lower rumen volatile fatty acid (VFA) production, while no such effect was observed in in vivo studies (Wanapat et al 2008b;Kongmun et al 2010). Benchaar et al (2006) have also reported that essential oil did not significantly change rumen fermentation.…”
Section: Rumen Fermentation Characteristicsmentioning
confidence: 94%
See 2 more Smart Citations
“…Since long manipulation of gut function and microbial habitat of domestic animal with feed additives of phytogenic origin can be a potential alternatives for enhancing rumen ecology (Wanapat et al, 2008), performance and health status of livestock (Manzanilla et al, 2001). However use of chemicals and antibiotics as livestock feed additives has been banned in European Union and in many countries because of the risk of accumulation of residues in animal products there by resulting in development of antibiotics resistance by several pathogenic microorganisms (Russell and Houlihan, 2003).…”
Section: Introductionmentioning
confidence: 99%